Economic impact of pharmaceutical interventions in a medium complexity Brazilian university hospital - Leandro Gouveia Carneiro; Karine Dal Paz; Eliane Ribeiro (Universidade de São Paulo, 2023)
Abstract Clinical pharmacists have been increasing their participation mainly through actions aimed at patient care, with international studies demonstrating favorable cost-benefit ratio from pharmacists interventions. However, there are few studies carried out in Brazil about the subject. This study aims to assess the economic impact of pharmaceutical interventions (PIs) in a hospital setting performed in October 2018. Each performed PI was registered and associated with the direct cost of drugs for economic impact analysis. A total of 185 PIs were evaluated, comprising 106 patients. The most intervened drugs were antibiotics, presenting the greatest economic impact, R$2,370. The total economic impact was R$2,578, mainly in the Pediatric Intensive Care Unit that represented R$1,701. Regarding the economic impact by PI as the "Suspension of drug without indication" saved R$1,360 while the "Inclusion of required drugs" cost R$807. It was estimated that the savings would be R$30,936 and, if PIs were performed at day zero, the savings would be R$79,728 per year. An average of 1.75 PI per patient was performed with an economic impact of R$14 per PI. Our results showed that clinical pharmacist's role in the evaluation of pharmacotherapy is important for patients' health and represents a positive economic impact.